Effect of Sawdust Particle Size on Physical, Mechanical, and Energetic Properties of Pinus durangensis Briquettes - Zepeda Cepeda, Christian Osvaldo; Goche Télles, José Rodolfo; Palacios Mendoza, Celina; Moreno Anguiano, Oswaldo; Núñez Retana, Víctor Daniel; Heya, Maginot Ngangyo; Carrillo Parra, Artemio (2021)
Particle size is a physical property that sometimes limits the quality of briquettes, so it is recommended to use different sizes in mixtures for their manufacture. The objective of this research was to evaluate the effect of different particle sizes of sawdust in mixtures on some physical, mechanical, and energetic properties of briquettes made from Pinus durangensis sawdust, as well as set the ranges within the appropriate values found to obtain desired values. Three particle sizes were established (large, medium, and small), and 10 mixtures were prepared using different percentages of each particle classification. The particle density, volumetric swelling, compressive strength, impact resistance index (IRI), and gross calorific value of the briquettes were evaluated. For the determination of optimal mixtures, the surface response methodology was used under a three-factor simplex-lattice model. The particle density values were in the range 0.92 to 1.02 g cm−3 and the volumetric swelling was 0.96 to 3.9%. The highest resistance to compression was 37.01 N mm−1, and the IRI was found in the range of 53 to 107%. The gross calorific values were from 19.35 to 21.63 MJ kg−1. The selection of different particle sizes for the mixtures increases the quality of the briquettes.